2011
DOI: 10.1016/j.scr.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chromosome instability on the maintenance and differentiation of human embryonic stem cells in vitro and in vivo

Abstract: The therapeutic potential of human embryonic stem cells (hESCs) has long been appreciated, and the recent FDA approval of hESC derivatives for cell-based therapy encourages the clinical application of hESCs. Here, using CHA3-hESCs with normal and abnormal karyotypes, we report the importance of maintaining normal chromosomes during in vitro culture and the differentiation of hESCs for minimization of posttransplantation complications. We found that undifferentiated CHA3-hESCs with trisomy chromosome 12 undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Although one study reported that teratomas from T12-hESCs are not significantly different in their gross composition 32 , another study reported that T12-hESCs undergo abnormal cell division 33 ; both studies, however, assessed only one cell line each, using limited experimental assays. In the current study, we compared the global gene expression signatures of dozens of hPSC and GCT cell lines, and revealed that trisomy 12 renders hPSCs more transcriptionally similar to GCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Although one study reported that teratomas from T12-hESCs are not significantly different in their gross composition 32 , another study reported that T12-hESCs undergo abnormal cell division 33 ; both studies, however, assessed only one cell line each, using limited experimental assays. In the current study, we compared the global gene expression signatures of dozens of hPSC and GCT cell lines, and revealed that trisomy 12 renders hPSCs more transcriptionally similar to GCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Moon et al demonstrated aberrant cell division in karyotypically abnormal hESCs during in vitro culture. These authors subsequently showed a post-transplant tumor-like tissue growth arising from the hESC transplant derivatives (68). These results emphasize that sustaining normal human chromosome number during in vitro culture and differentiation is indispensable for safe transplantation of hESC derivatives for therapeutic use.…”
Section: Obstacles To Hesc Researchmentioning
confidence: 86%
“…91 Safety concerns common to both cells, such as teratoma formation, also require further investigation. 51,89 The ideal developmental stage for transplantation is also unclear. 56,120,122 In the field of photoreceptor regeneration, transplantation of post-mitotic rod precursors appears to result in superior differentiation and integration with the host retina.…”
Section: Rgc Transplantationmentioning
confidence: 99%